Preparation of controlled release microspheres using supercritical fluid technology for delivery of anti-inflammatory drugs - Duarte, Ana Rita C. (2006)
Ethylcellulose/methylcellulose blends were produced using different precipitation techniques and impregnated with naproxen, a non-steroidal anti-inflammatory drug (NSAID). Solvent-evaporation technique was used not only for the preparation of ethylcellulose/methylcellulose microspheres but also to encapsulate naproxen. Supercritical fluid (SCF) impregnation was also performed to prepare naproxen loaded microspheres. The microspheres, impregnated by the SCF technique, were prepared both by solvent-evaporation and by a supercritical antisolvent (SAS) process. In vitro release profiles at pH 7.4 and 1.2, of naproxen-loaded microspheres were evaluated and the results were modelled Fick’s law of diffusion and Power law. Miscrospheres prepared by supercritical antisolvent have a higher loading capacity and present a slower release profile. The systems studied present a release mechanism controlled by drug diffusion which complies Fick’s law of diffusion.